2010
DOI: 10.1002/pssb.200983273
|View full text |Cite
|
Sign up to set email alerts
|

The role of stacking faults and their associated 0.13 eV acceptor state in doped and undoped ZnO layers and nanostructures

Abstract: Cathodoluminescence spectra recorded with high spatial and wavelength resolution on tilted ZnO epitaxial layers allow to identify a very prominent emission peak at 3.314 eV as a free electron to shallow acceptor (E A % 130 meV) transition. By correlation with TEM cross-section images recorded on the same samples we can find these acceptor states to be located on basal plane stacking faults (BSFs). Locally, high concentrations of acceptor states are found. Since this spectral feature is often reported in litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
5
29
2
Order By: Relevance
“…They concluded that lines at 3.314 eV and at 3.30 eV (at 15 K) are associated with (e,A o ) and DAP emissions, respectively, induced by BSFs. Similar to Schirra et al, 29 Thonke et al 30 also reported an acceptor binding energy of 130 meV. Although the chemical origin of the acceptor is unknown, the Zn vacancy was suggested as a possible candidate by both.…”
Section: Figuresupporting
confidence: 62%
See 4 more Smart Citations
“…They concluded that lines at 3.314 eV and at 3.30 eV (at 15 K) are associated with (e,A o ) and DAP emissions, respectively, induced by BSFs. Similar to Schirra et al, 29 Thonke et al 30 also reported an acceptor binding energy of 130 meV. Although the chemical origin of the acceptor is unknown, the Zn vacancy was suggested as a possible candidate by both.…”
Section: Figuresupporting
confidence: 62%
“…33 Also reported recently is the formation of a quantum wire at the intersection between a 3.8 nm thick (Al,Ga)N/GaN quantum well and BSFs, leading to radiative recombination of localized excitons. 34 Although the energetic position reported by Khranovskyy et al 5 is considerably higher than what has been reported by Schirra et al, 29 Thonke et al 30 and also in this work, Khranovskyy et al 5 clearly demonstrated the presence of a high density of BSFs perpendicular to the c-axis. They also studied temperature and laser power dependent PL and concluded that the line has an excitonic nature.…”
Section: Figuresupporting
confidence: 41%
See 3 more Smart Citations